Oxygen, sulfur, and iron radial abundance gradients of classical Cepheids across the Galactic thin disk - Silva, Ronaldo da; D’Orazi, V.; Palla, M.; Bono, G.; Braga, V. F.; Fabrizio, M.; Lemasle, Bertrand; Spitoni, E.; Matteucci, F.; Jönsson, H.; Kovtyukh, V.; Magrini, L.; et al. (Astronomy and astrophysics, 2023)
Methods. Optical high-resolution spectra with a high signal-to-noise ratio that were collected with different spectrographs were adopted to provide homogeneous estimates of the atmospheric parameters (effective temperature, surface gravity, and microturbulent velocity) that are required to determine the abundance. Individual distances were based either on trigonometric parallaxes by the Gaia Data Release 3 (Gaia DR3) or on distances based on near-infrared period-luminosity relations. - Results. We found that iron and α-element radial gradients based on CCs display a well-defined change in the slope for galactocentric distances larger than ∼12 kpc. We also found that logarithmic regressions account for the variation in [X/H] abundances from the inner to the outer disk. Radial gradients for the same elements, but based on open clusters covering a wide range in cluster ages, display similar trends. This means that the flattening in the outer disk is an intrinsic feature of the radial gradients because it is independent of age. Empirical evidence indicates that the S radial gradient is steeper than the Fe radial gradient. The difference in the slope is a factor of two in the linear fit (−0.081 vs. −0.041 dex kpc−1) and changes from −1.62 to −0.91 in the logarithmic distance. Moreover, we found that S (explosive nucleosynthesis) is underabundant on average when compared with O (hydrostatic nucleosynthesis). The difference becomes clearer in the metal-poor regime and for the [O/Fe] and [S/Fe] abundance ratios. We performed a detailed comparison with Galactic chemical evolution models and found that a constant star formation efficiency for galactocentric distances larger than 12 kpc accounts for the flattening observed in both iron and α-elements. To further constrain the impact of the predicted S yields for massive stars on radial gradients, we adopted a toy model and found that the flattening in the outermost regions requires a decrease of a factor of four in the current S predictions. - Conclusions. CCs are solid beacons for tracing the recent chemical enrichment of young stellar populations. Sulfur photospheric abundances, when compared with other α-elements, have the key advantage of being a volatile element. Therefore, stellar S abundances can be directly compared with nebular sulfur abundances in external galaxies.
Gesehen am 30.09.2024